Pengaruh Kompensasi Dan Pengembangan Karir Terhadap Kinerja Karyawan Rs Prima Husada Malang - Lukitaningtias, Firina; Hariyanto, Agoes; Ratih, Puput Sekar Nari (Magister Manajemen Universitas Wisnuwardhana, 2023)
Hospitals play a frontline role in healthcare services and serve as the starting point for the community's interaction with the healthcare system, thereby significantly contributing to the improvement of public health status. As the population increases, the demand for healthcare services also rises. Public awareness of health and a higher level of education make them increasingly understand health issues, accompanied by expectations for quality and satisfactory healthcare services. Hospital management must pay attention to employee welfare, especially in terms of compensation and career development, in order to provide resources capable of meeting the demands of optimal service. The purpose of this study is to examine the influence of compensation and career development on employee performance at Prima Husada Hospital Malang, both partially and simultaneously. This research uses a quantitative approach employing multiple linear regression analysis and is processed using SPSS. The results show that compensation and career development have a significant impact on employee performance, both partially and simultaneously. These results are expected to assist in the development of strategies to improve employee performance, particularly in companies operating in the public service sector.